Mechanisms to combat drug trafficking in Iraq - Aliaa Mahmoud; Huda Jaber (الرافدین للحقوق)
Drug trafficking is considered one of the most dangerous types of crimes and has the most significant impact on individuals, society, and even the international community as a whole. Mafia gangs, which do everything in their power to trade in drugs, resort to theft, murder, and various other methods to engage in this trade and earn more money. On the other hand, the high rates of drug use cause a general disruption of the workforce, especially among the youth, due to its widespread prevalence. To combat this crime, countries have generally resorted to enacting strict laws Drug trafficking is considered one of the most dangerous types of crimes and has the most significant impact on individuals, society, and even the international community as a whole.